Various student strategies in making graph of quadratic functions - A Saputra; A Jupri; N Priatna (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Writing down the things that we think is a very important act. Including writingdown things to be conveyed to others. In conveying something, every individual has their ownway. Likewise in terms of describing the graph of quadratic functions. In this article, we wouldlike to explain the ways students used to create graphs of quadratic function. We found fourtypes of images produced from thirty-six students who worked on the questions we gave. Thisis related to the strategies students use to draw a graph of quadratic functions. Related to thesestrategies, we plan to explore it more deeply in terms of student learning styles.